The impact of a plant-based diet on the menstrual cycle and female fertility - Grzesik, Karina; Pilarczyk, Katarzyna; Rabęda, Aleksandra; Klepacz, Natalia; Cudziło, Zuzanna; Sawczuk, Hubert; Nowak, Weronika Ewa; Kaus, Marta; Adamska, Hanna; Malicka, Marta (Journal of Education, Health and Sport, 2024)
Introduction and objective: A plant-based diet is being adopted by an increasing number of people worldwide. Its health benefits have been described in numerous scientific studies. Unfortunately, an improperly balanced diet that excludes animal-derived products can, through various mechanisms, lead to deficiencies and disruptions in the functioning of many systems in the body. This review paper aims to present and summarize the findings and current literature on the impact of a plant-based diet on the menstrual cycle and female fertility. Brief description of the state of knowledge: There is insufficient research on how minerals and vitamins influence the biochemical processes of the menstrual cycle and related symptoms. While nutrient deficiencies in plant-based diets are widely discussed, most studies focus on general health rather than the reproductive system, which is crucial for hormonal balance and fertility. This highlights the need for more research to improve our understanding of the female reproductive and endocrine systems and ensure better care for women. Methods: A literature review was conducted using PubMed and Google Scholar with search terms like "impact of plant-based diet", "menstrual cycle disorders", "causes of female infertility", "deficiencies in vegans and vegetarians" and related variations. Articles published within the last five years were prioritized. Conclusions: A properly followed plant-based diet, supported by supplementation, has a positive effect on the female reproductive system, without causing menstrual cycle disorders or infertility. Unfortunately, the more exclusions present in the diet, the more likely it is to cause deficiencies in minerals and vitamins. Inadequate levels of these nutrients can lead to abnormalities in the female reproductive system, both in laboratory tests and in symptoms experienced by women.